2018
DOI: 10.1177/1756284818785571
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin for detection of postoperative endoscopic recurrence in Crohn’s disease: systematic review and meta-analysis

Abstract: Background:Anastomotic recurrence is frequent in patients with Crohn’s disease (CD) following ileocecal resection. The degree of endoscopic recurrence, quantified by the Rutgeerts score (RS), correlates with risk of clinical and surgical recurrence. Several studies demonstrate the accuracy of fecal calprotectin (FC) for detection of endoscopic recurrence, however the optimal threshold FC value remains to be established. The aim of our meta-analysis was to evaluate the accuracy of common FC cut-offs for detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 54 publications
1
22
0
2
Order By: Relevance
“…Another recent meta-analysis showed that an FC cutoff of 150 μg/g could be used to detect a postoperative endoscopic recurrence of Crohn's disease (pooled sensitivity was 0.70 [95% CI, 0.59 to 0.81], specificity, 0.69 [95% CI, 0.61 to 0.77], and DOR, 5.92 [95% CI, 2.61 to 12.17]). 46 Researchers disagree on whether FC can accurately detect intestinal inflammation in both the small and large bowels. Some studies report that FC can detect Crohn's disease throughout the intestinal tract, 20,47 but others have suggested a lower degree of accuracy for diagnosis in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent meta-analysis showed that an FC cutoff of 150 μg/g could be used to detect a postoperative endoscopic recurrence of Crohn's disease (pooled sensitivity was 0.70 [95% CI, 0.59 to 0.81], specificity, 0.69 [95% CI, 0.61 to 0.77], and DOR, 5.92 [95% CI, 2.61 to 12.17]). 46 Researchers disagree on whether FC can accurately detect intestinal inflammation in both the small and large bowels. Some studies report that FC can detect Crohn's disease throughout the intestinal tract, 20,47 but others have suggested a lower degree of accuracy for diagnosis in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study did not detect a significantly different levels of fecal calprotectin in patients with and without post-operative recurrence while the other studies did ( Table 2 ). A meta-analysis performed by Tham et al on examining the use of fecal calprotectin for detection of post-operative endoscopic recurrence in CD showed that a significant threshold effect was observed for fecal calprotectin values of 50, 100, 150, and 200 μg/g; while the optimal diagnostic accuracy was obtained for fecal calprotectin value of 150 μg/g, with a pooled sensitivity and specificity being 70 and 69%, respectively ( 100 ).…”
Section: Calprotectin Lactoferrin and S100a12 In Predicting Post-opmentioning
confidence: 99%
“…Importantly, TFH cell frequencies in the peripheral blood were also significantly increased in CD patients with active intestinal inflammation as determined by fecal calprotectin concentrations above 200 mg/kg, a threshold with high sensitivity and specificity to predict the presence of postoperative recurrence ( Figure 1 B ). 19
Figure 1 TFH cell frequencies correlate with CD activity. ( A ) TFH cell frequencies in ileal biopsies of CD patients (n = 15) were significantly increased in patients with active inflammation (Simple Endoscopic Score for Crohn’s Disease [SES-CD] ≥3 points) as compared with patients in endoscopic remission (SES-CD ≤2 points).
…”
Section: Resultsmentioning
confidence: 99%